Epidemiology of neonatal mortality: a spatial and multilevel analysis of the 2019 mini-Ethiopian demographic and health survey data - Temesgen Worku Gudayu (BMC, 2023)
Abstract Background Sub-Saharan African countries are a high-burden region of neonatal mortality and showed slow progress in its reduction. In developing countries, as long as the current trend of mortality persists, achieving a sustainable development target for neonatal mortality would be challenging. The aim of this study was to detect significant geographic areas and identify community and individual-level predictors of neonatal mortality in Ethiopia to draw attention to a policy. Methods A weighted total sample of 24,136 mothers from the 2019 mini-Ethiopian demographic and health survey data were included in the analysis. Global Moran's I statistics was run to check the clustering of neonatal mortality and then kriging interpolation was done to predict the magnitude of neonatal mortality in Ethiopia. In addition, SaTScan analysis was also executed to identify hot spot clusters of neonatal mortality. Finally, a multilevel mixed-effect logistic regression model was used to identify community and individual-level predictors of early neonatal and neonatal mortality. Results The lifetime early neonatal and neonatal mortality among mothers in Ethiopia was 5.08 (95% CI: 4.13-6.03) and 6.54 (5.55, 7.52) per 1000 births respectively. Neonatal mortality was spatially clustered in the country and the SaTScan analysis identified significant hotspot areas of neonatal mortality in the Amhara and Afar regions and some areas of the Somali and Oromia regions. Its predicted magnitude was > 8 per 1000 births in wide areas of the Amhara and Benishangul regions. A multilevel mixed-effect logistics regression analysis identified that a lower level of maternal education, being a twin neonate, and being a male neonate were predictors of both early neonatal and neonatal mortality. Whereas, the younger age of mothers predicted neonatal mortality. Conclusions Neonatal mortality in Ethiopia is geographically clustered and sociodemographic and obstetric factors played a significant role. Policy direction should focus on evidence-based practices like midwives-led community and facility-based continuum of care from preconception to postnatal periods to possibly reduce neonatal mortality.